The modern Ayurveda milestones beyond the classical age - Khare, C. P., 1932-; Katiyar, Chandra Kant. (Taylor & Francis, 2012)
"The Ayurveda provides the cornerstone of India's ancient medical science. The concept this book on Modem Ayurveda took shape after the editors had a number of meetings over an extended period of time with scientists and researchers of various herbal institutes and pharmaceutical companies. They felt that between the classical period and modem period there should be a demarcation line. This book will present the post classical period including the application of modem scientific analytical tools for standardization, modern pharmacological tools for safety and efficacy evaluation, and the application of biotechnology to elicit the mechanism of drug actions"--Provided by publisher.